2003
DOI: 10.1354/vp.40-4-363
|View full text |Cite
|
Sign up to set email alerts
|

3-Methylindole Induces Transient Olfactory Mucosal Injury in Ponies

Abstract: Abstract. Response to 3-methylindole (3MI) varies among species. Mice recover from 3MI-induced bronchiolar epithelial injury but sustain persistent olfactory mucosal injury with scarring and epithelial metaplasia. In contrast, 3MI induces obliterative bronchiolitis in horses and ponies, but olfactory mucosal injury has not been reported. To evaluate the effect of 3MI on equine olfactory mucosa, ponies were dosed orally with 100 mg 3MI/kg (n ϭ 9) or corn oil vehicle (n ϭ 6). All ponies treated with 3MI develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Moreover, Ki-67 expression is widely used for the characterization of the humans, rodents and carnivore OE and both markers are useful to detect dividing cells ( Carter et al, 2004 ; Murdoch and Roskams, 2007 ; Bock et al, 2009 ; Holbrook et al, 2011 ). PCNA expression has already been described for the equine sensory epithelium of the vomeronasal organ ( Miller et al, 2003 ) and was also found in the rat OE (own unpublished data). Typically, PCNA positive cells were found in small groups indicating that proliferating areas intermingle with non-proliferating regions ( Graziadei and Graziadei, 1979 ).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Moreover, Ki-67 expression is widely used for the characterization of the humans, rodents and carnivore OE and both markers are useful to detect dividing cells ( Carter et al, 2004 ; Murdoch and Roskams, 2007 ; Bock et al, 2009 ; Holbrook et al, 2011 ). PCNA expression has already been described for the equine sensory epithelium of the vomeronasal organ ( Miller et al, 2003 ) and was also found in the rat OE (own unpublished data). Typically, PCNA positive cells were found in small groups indicating that proliferating areas intermingle with non-proliferating regions ( Graziadei and Graziadei, 1979 ).…”
Section: Discussionsupporting
confidence: 52%
“…The globose basal cells are thought to be the progenitors of the ORNs ( Graziadei and Graziadei, 1979 ; Calof and Chikaraishi, 1989 ; Mackay-Sim and Kittel, 1991 ) and the sustentacular cells ( Schwob et al, 1994 ; Chen et al, 2004 ). Due to their proliferative activity, globose basal cells can be visualized by BrdU ( Carter et al, 2004 ) or [ 3 H]-thymidine incorporation ( Graziadei and Graziadei, 1979 ) and express proliferating cell nuclear antigen (PCNA) or Ki-67 ( Miller et al, 2003 ; Carter et al, 2004 ; Bock et al, 2009 ; Holbrook et al, 2011 ). The horizontal basal cells possess features of multipotent stem cells and can induce regeneration after epithelial damage ( Schwartz Levey et al, 1991 ; Holbrook et al, 1995 ; Carter et al, 2004 ; Murdoch and Roskams, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bronchiolar epithelial injury in mice is transient, but olfactory mucosal injury with scarring and metaplasia persists. In contrast, Miller et al (2003) found that 3 days of 100mg skatole/kg in horses resulted in persistent damage (necrosis, scarring and metaplasia) to the bronchiolar epithelium but only transient injury occurred in olfactory mucosa.…”
Section: Skatole and Androstenonementioning
confidence: 82%
“…Indole derivatives are extremely physiologically active compounds that are widely used in medical practice. They can exert stimulating and inhibiting action on the nervous system and possess hemorrhagic, sedative, and radioprotective properties in addition to others [1,2]. For example, indole-3-carbinol facilitates detoxification of poisons, including those with carcinogenic properties, and reduces the threat of developing a series of hormone-dependent tumors of epithelial origin [3].…”
mentioning
confidence: 99%